How Individual Differences Interact With Task Demands in Text Processing. (4th March 2017) - Wang, Zuowei; Sabatini, John; O'Reilly, Tenaha; Feng, Gary
ABSTRACT: Reading is affected by both situational requirements and one's cognitive skills. The current study investigated how individual differences interacted with task requirements to determine reading behavior and outcome. We recorded the eye movements of college students, who differed in reading efficiency, while they completed a multiple-choice (MC) comprehension test in two within-subject conditions: one in which they read passages and answered MC questions as in a typical reading test and one in which they wrote a summary before answering the MC questions. We found students spent longer time reading the text in the summary-writing condition, resulting in a benefit in the time they spent when answering MC questions. This time benefit was larger for students who had relatively low reading efficiency. These results demonstrated that both task requirements and individual differences can interact to affect reading behavior and performance. Implications for reading practice and assessment are discussed.